Facing The Retirement Period of Government Employees (Analysis of Local Government Regulations and Their Implementation) - Septiany, Fenny; Khumayah, Siti; Rahmayanti, Rahmayanti (Jurnal Polisci, 2024)
Retirement is the condition of an employee after passing the productive phase at work. This study discusses the analysis of local government regulations that regulate employee rights in preparation for retirement. This study aims to analyze the Regional Government Regulations regulating retirement employees and review their implementation. Korten's theory of the model of policy implementation suitability is the knife of this research analysis conducted at SMPN 16 Cirebon City. This research uses a qualitative approach with a case study design. The research locus at SMPN 16 Cirebon City by taking research data through interview methods to the Personnel and Human Resources Development Agency (BKPSDM), the Cirebon City Education Office (Disdik), and the Principal, documentation and observation studies. The study results show that regulations for preparing retired employees, such as administrative ones, have been set.